A preliminary report of a randomized controlled phase 2 trial of the safety and immunogenicity of mRNA-1273 SARS-CoV-2 vaccine. Issue 20 (12th May 2021) - Chu, Laurence; McPhee, Roderick; Huang, Wenmei; Bennett, Hamilton; Pajon, Rolando; Nestorova, Biliana; Leav, Brett; ,
Highlights: Vaccines to prevent the global spread of SARS-CoV-2 infection are in development. mRNA-1273 vaccine at 50 and 100 µg elicits robust immune responses in healthy adults. Immunogenicity is generally similar in younger (18–55 yr) and older (≥55 yr) adults. Safety profile of mRNA-1273 is acceptable; no serious adverse effects were observed. Results support 2-dose regimens of 50 or 100 µg mRNA-1273 SARS-CoV-2 vaccine. Abstract: Background: Vaccines are urgently needed to prevent the global spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We assessed the safety and immunogenicity of vaccine candidate mRNA-1273, encoding the prefusion-stabilized spike protein of SARS-CoV-2. Methods: This phase 2, randomized, observer-blind, placebo-controlled trial was conducted at 8 sites in the USA, in healthy adults aged ≥18 years with no known history or risk of SARS-CoV-2 infection, and had not previously received an investigational CoV vaccine or treatment. Participants were stratified into two age cohorts (≥18-<55 and ≥55) and were randomly assigned (1:1:1) to either 50 or 100 µg of mRNA-1273, or placebo administered as two intramuscular injections 28 days apart. The primary outcomes were safety, reactogenicity, and immunogenicity assessed by anti-SARS-CoV-2-spike binding antibody level (bAb). Secondary outcome was immunogenicity assessed by SARS-CoV-2 neutralizing antibody (nAb) response. Results: Between 29 May and 8 July 2020, 600 participants were randomized, 300 per age cohort. The most common solicited adverse reactions were pain at injection site, headache, and fatigue following each vaccination in both age cohorts. One serious adverse event deemed unrelated by the site investigator occurred 33 days post-vaccination one. mRNA-1273 induced bAb and nAb by 28 days post-vaccination one that were higher at the 100 µg dose relative to the 50 µg dose; this difference was less apparent post-vaccination two. Binding antibodies and nAb increased substantially by 14 days following the second vaccination (day 43) to levels exceeding those of convalescent sera and remained elevated through day 57. Conclusions: Vaccination with mRNA-1273 resulted in significant immune responses to SARS-CoV-2 in participants 18 years and older, with an acceptable safety profile, confirming the safety and immunogenicity of 50 and 100 µg mRNA-1273 given as a 2 dose-regimen. ClinicalTrials.gov; NCT04405076.